Competing forms of populism and territorial politics: the cases of Vox and Podemos in Spain. Issue 3 (2nd July 2020) - Vampa, Davide
ABSTRACT: Until 2018 right-wing populism was regarded as an irrelevant phenomenon in Spain. The recent success of Vox provides clear evidence that the transformation of Spanish politics is still under way. Today, both right-wing and left-wing populism – the latter represented by Podemos – coexist in an increasingly fragmented party system. This article shows that territorial mobilization has been an important factor in the emergence of these two competing forms of populism. In fact, their positioning on the so-called 'centre-periphery cleavage' at the moment of their initial success is their most notable element of differentiation. Right-wing populism in Spain is strongly anti-localist and anti-regionalist and this is clearly reflected in the territorial distribution of its support. On the other hand, left-wing populism had its electoral breakthrough particularly in those areas where demands for autonomy and even independence were stronger. This makes the Spanish case extremely interesting since most studies have not sufficiently considered the territorial dimension as a defining, and distinguishing, feature of right-wing and left-wing forms of populism.